TRANSLATION AND ADAPTATION BY ALEXANDRE DUMAS FROM A DISCURSIVE AND SOCIAL PERSPECTIVE - Sellin, Kátia Cristina Pelegrino (Seven Editora, 2025)
Analyzing translation and adaptation, in addition to the role of the translator from a discursive and social perspective, is our focus in this research. Through the translations and adaptations of Alexandre Dumas, as well as the work done by Carlos Heitor Cony, journalist, writer and translator, who mastered Latin, Greek, French and Italian, we observe translations and adaptations of novels from universal literature, of adventure stories with cloak and sword, to glimpse how much the current translator can recreate the original,  as well as adapting it to the target audience, in the case of Cony, to young people, children and young people, from around the 1970s to the present day. It should be noted that the historical period around the author's adaptations was militarism, proclaimed after the military coup of 1964. The current translator can transform the original, and Cony made his adaptations in this way, making them accessible to young people. There was a certain focus on Brazilian culture and political history, in order to obtain an idea of the aforementioned historical phase, in which literature played an important role. The main focus of analysis was Cony's adaptation of the last part of the saga of "The Three Musketeers", by Alexandre Dumas (1844), entitled "The Iron Mask".DOI: https://doi.org/10.56238/sevened2025.018-033